On the relationship between J-integral and crack opening displacement - Glavardanov, Ivan; Gerić, Katarina; Fiši, Juija (Journal of Production Engineering, 1993)
This paper describes a simple method of calculating the material-dependent two-dimensional factor β used in the well-known relation σ = βε, or, in other words, of improving the most simple relation σ = ε. As derived in this paper, β accounts for the effect of hardening and prior cold work of the material. The results obtained by this very simple procedure compare quite favorably with experimental and numerical results of other authors.